Preparation and Characterization of Soybean Oil-based Flame Retardant Rigid Polyurethane Foams Containing Phosphaphenanthrene Groups - Gong, Qirui; Wang, Niangui; Zhang, Kaibo; Huang, Shizhao; Wang, Yuhan (Letters in Organic Chemistry, 2020)
A phosphaphenanthrene groups containing soybean oil based polyol (DSBP) was synthesized by epoxidized soybean oil (ESO) and 9,10-dihydro-oxa-10-phosphaphenanthrene-10-oxide (DOPO). Soybean oil based polyol (HSBP) was synthesized by ESO and H2O. The chemical structure of DSBP and HSBP were characterized with FT-IR and 1H NMR. The corresponding rigid polyurethane foams (RPUFs) were prepared by mixing DSBP with HSBP. The results revealed apparent density and compression strength of RPUFs decreased with increasing the DSBP content. The cell structure of RPUFs was examined by scanning electron microscope (SEM) which displayed the cells as spherical or polyhedral. The thermal degradation and flame retardancy of RPUFs were investigated by thermogravimetric analysis, limiting oxygen index (LOI), and UL 94 vertical burning test. The degradation activation energy (Ea) of first degradation stage reduced from 80.05 kJ/mol to 37.84 kJ/mol with 80 wt% DSBP. The RUPF with 80 wt% DSBP achieved UL94 V-0 rating and LOI 28.3. The results showed that the flame retardant effect was mainly in both gas phase and condensed phase.
Keywords: Flame retardancy